A Framework for the Identification and Strategic Development of Translation Specialisms - Byrne, Jody (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2014)
The purpose of this paper is to explore the challenges facing newly qualified translators in identifying and developing their translation specialisms. By means of a survey of translation agencies’ recruitment processes, the paper illustrates the need for freelance translators to be able to identify and describe their specialisms in a high level of detail when applying for work with translation agencies. The difficulties this presents to newly qualified translators are then highlighted. After considering the variety of terms used to classify translation specialisms and the need to prepare students for industry, this paper proposes a framework for the purpose of helping students and newly qualified translators to identify and describe their specialisms as well as develop new ones. The paper concludes by describing how the framework can be incorporated into translator training programmes using a form of Personal Development Planning.